Analysis of caregiver behavior in preventing stunting in children - Santi, Eka; Firdausi, Rieh; Azlina, Fitri Ayatul; Hasibuan, Nana Astriana; Handayani, Tina (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Stunting is one of the chronic malnutrition conditions that is a problem in various countries. The impact of stunting will create a generation with a low quality of life in the future. Stunting prevention is important because it will reduce the effects that will occur in terms of cognitive development, intelligence, and health. Caregivers, especially mothers, have a big role in making efforts to prevent stunting in children. Mothers or caregivers play a role in monitoring children's growth and development. Several related factors include knowledge, family support, attitude, and providing complementary foods to support this effort.  Objectives: The purpose of this study is to analyze the relationship between knowledge, family support, attitudes, and the provision of complementary foods to prevent stunting in children. Methods: A quantitative research method with a cross-sectional design in caregivers with 75 family members under five years old in the work area in Health Center. The samples were selected using the purposive sampling technique. Data was collected by questionnaires of knowledge, family support, attitudes, supplementation and stunting risk prevention. Data analysis uses chi square bivariate with a significance level of p < 0.05. Results: The results showed that there was a relationship between knowledge (p=0.008), family support (p=0.014), attitude (p=0.005), complementary feeding (0.002) and stunting prevention. Conclusions: Stunting prevention behavior is an effort made by parents by considering factors from themselves and others, one of which is family support. Caregivers who understand stunting will show attitudes in fulfilling nutrition and monitoring children's growth and development.